Generational Consciousness, Narrative, and Politics - Edmunds, June,; Turner, Bryan S., (Rowman & Littlefield Publishers, 2002)
With the erosion of strong class theory, sociologists have recently started to look at aspects of social stratification other than class. One of the most interesting new areas of investigation is the sociology of generations. This book brings together the work of scholars who are making a major contribution to this new sociological interest. Through a combination of innovative theoretical and empirical studies, this book shows that an analysis of generations is essential to an understanding of major social, political and intellectual trends in the postwar period. Each author brings to the volume insights from their own area of specialism - with rich illustrative material spanning topics as diverse as African American identity and Spanish youth culture. Theoretical inspiration also comes from a range of traditions, including cultural and historical sociology; social interactionism; social and cognitive psychology and life course theory. However, a unifying thread emerges around questions about how generations should be conceptualized; the role of trauma generating generational consciousness; the relationship between auto-biography and generational identity and the nature of inter and intra-generational relationships. This volume, therefore, provides a lively contribution to debates about the nature of generations and a stimulating basis for further work in this area.